IMPLEMENTASI KEBIJAKAN PEMERINTAH SEBAGAI UPAYA PENCEGAHAN KEJAHATAN KORPORASI MELALUI PRINSIP BENEFECIAL OWNERSHIPS - I Gusti Ayu Eviani Yuliantari (Universitas Suryakancana, 2023)
Repeating Indonesia's national development shows rapid progress. Globalization and modernization through advances in technology, communication, transportation and informatics, especially in the fields of economy, trade and investment, world progress and development, seem to make national boundaries, sovereignty and sovereign rights blur. In relation to the current era of globalization, the existence of a corporation has a big contribution to the interests of the state and its citizens. The crimes mentioned above often contain elements of deceit, misrepresentation, concealment of facts, manipulation, breach of trust, subterfuge or illegal circumvention. very detrimental to society at large. Seeing the things mentioned above, it is not an exaggeration to say that corporate crime is a form of crime that not only threatens economic stability and financial system integrity, but can also endanger the foundations of social, national and state life. Therefore, it is necessary to regulate the prevention of corporate crime through government policies and their implementation. Keywords: Government Policy, Corporate Crime, Benefecial Ownership